Extracurricular Activities for Students with ASD and the Efficiency Assessment of the Program «Let's go to the Museum!» - E.V. Khilkevich (Moscow State University of Psychology and Education, 2021)
Extracurricular activities compose the basis of an educational institution, aimed at personal development and developing of conditions for self-determination and socialization of the student. Out-of-school activities such as museum excursions are highly important in this process. Federal Resource Center for Organization of Comprehensive Support to Children with Autism Spectrum Disorders professionals developed the inclusion model for students with ASD enrolled in Out-of-school activities. The program of sociocultural integration "Let's go to the Museum!" was developed based on this model. A number of assessment tools - The program efficiency was revealed by following tools and methods - observation, recording behavior change using a checklist, parents interview. Four years of observing students showed that their social behavior development and improving the quality of life of their families skills changed.